Existentialism, Epiphany, and Polyphony in Dostoevsky's Post-Siberian Novels - Siddiqi, Bilal (Religions, 2019)
Dostoevsky can be meaningfully read as a defender of Russian Orthodoxy; a psychologist; a polemicizing anti-nihilist ideologue; a Schillerian romantic; a Solovyovian believer in love, goodness, and beauty; a prophet. I approach Dostoevsky through a new lensDostoevsky as an existential phenomenologist. Although writers such as Kauffman, Camus, and Shestov have cast Dostoevsky as an existentialist, their readings often focus too heavily on the critique of rationalist thinking in Dostoevsky's The Underground Man and explore Dostoevsky's existentialism largely in ethical rather than in existential-ontological terms. My interpretation will instead demonstrate that the primary focus of Dostoevsky's novels is on immanent existential-ontological truthshuman liferather than on transcendental, ideal truth, although the emphasis on the former does not negate the possible existence of the latter. This interpretation will also provide an original route towards a polyphonic reading of Dostoevsky.